Dry and wet torrefaction of microalgal biomass for biochar production as bioenergy sources / Gan Yong Yang - Gan , Yong Yang (2020)
Increasing population in global and living standards have risen the consumption of global energy. Thermochemical conversion approaches hold great potential for the biomass conversion into energy applications. Among these approaches, torrefaction is a promising technique to enhance the biomass properties, making it more practical and suitable in biofuel applications. In this study, two different species of microalgae (third generation biofuel feedstock) including Chlorella vulgaris ESP-31 and FSP-E were used as feedstocks for dry and wet torrefaction. Dry torrefaction of microalgae was performed at temperatures of 200, 250 and 300 ºC, and holding times of 15, 30, 45 and 60 min, respectively. Next, wet torrefaction of microalgae were conducted in water and dilute acidic solutions with the aid of microwaves irradiation at 160 ℃ and 10 min. The effects of sulfuric, phosphorus, and succinic acids on the microalgae with different percentages of chemical composition were investigated. The biochar produced from dry and wet torrefaction was performed fuel properties analysis and characterisation. In addition, TG FTIR and double-shot Py-GC/MS approaches were executed to investigate the effects of torrefaction pre-treatment on microalgae pyrolysis. Furthermore, the kinetic modelling of microalgal biochar pyrolysis was carried out by using an independent parallel reaction model. As a result, dry torrefaction enhanced the HHV of microalga ESP-31 biochar (high-carbohydrate) by 45% with energy yield of 80% at 300℃ and 60 min. Torrefaction performance was highly affected by torrefaction temperature compared with holding time for microalgae and Jatropha biomass, but the solid yield of microalga ESP-31 significantly decreased with holding time at mild torrefaction (250 ℃) due to the high reactivity of the microalgae components (carbohydrates) at that temperature. For the wet torrefaction, the disruption of the microalga FSP-E (high-protein) was not notable in the acidic solutions. The HHV of microalga ESP-31 biochar produced by succinic acid wet torrefaction pre-treatment was enhanced by 40% with at least 45% of energy yield. Thermogravimetric analysis revealed that the carbohydrate content of microalga ESP-31 has the highest degradation in sulfuric acid solution. For the evolved gas analysis, the microalgae pre-treated with sulfuric acid solution generated highest C–H absorption band in the pyrolysis gas. In the combustion TG-FTIR analysis, the intensity of O−H absorption band was removed in the first stage, indicating deoxygenation and dehydration process occurred in the wet torrefaction. In addition, the Py-GC/MS analysis revealed that only carbohydrate-derived products were decreased in the pyrolytic bio-oil of the microalgae pre-treated by the acidic solutions wet torrefaction. In contrast, carbohydrate and lipid-derived products were decreased in the pyrolytic bio-oil of the microalgae pre treated by the dry torrefaction. Lastly, the independent parallel reaction with four pseudo components model successfully predicted the kinetic behaviours of carbohydrates, proteins, lipids and other components in microalgae. The results revealed the thermal degradation curve with a fit quality of at least 98% were predicted for microalgae pyrolysis kinetics. In short, wet torrefaction successfully enhanced the fuel properties of the microalgal biochar for biofuel applications.